Latitudinal gradients of haemosporidian parasites: Prevalence, diversity and drivers of infection in the Thorn-tailed Rayadito (Aphrastura spinicauda) - Cuevas, Elfego; Vianna, Juliana A.; Botero-Delgadillo, Esteban; Doussang, Daniela; Gonzalez-Acuna, Daniel; Barroso, Omar; Rozzi Marin, Ricardo Roberto; Vasquez, Rodrigo A.; Quirici, Veronica (My University, 2020)
Latitudinal gradients are well-suited systems that may be helpful explaining distribution of haemosporidian parasites and host susceptibility. We studied the prevalence, diversity and drivers of haemosporidian parasites (Leucocytozoon, Plasmodium and Haemoproteus) along a latitudinal gradient (30 degrees-56 degrees S), that encompass the total distribution (similar to 3,000 km) of the Thorn-tailed Rayadito (Aphrastura spinicauda) in the South American temperate forests from Chile. We analyzed 516 individuals from 18 localities between 2010 and 2017 and observed an overall prevalence of 28.3% for haemosporidian parasites. Leucocytozoon was the most prevalent parasite (25.8%). We recorded 19 distinct lineages (13 for Leucocytozoon, five for Plasmodium, and one for Haemoproteus). Differences in haemosporidian prevalence and diversity by genus and type of habitat were observed in the latitudinal gradient. Further, we support the existence of a latitudinal associate distribution of Leucocytozoids in South America, where prevalence and diversity increase toward higher latitudes. Distribution of Leucocytozoon was associated with sub-antarctic habitat (higher latitude) and explained by cold temperature and high precipitation. On the other hand, we lacked to find a latitudinal associate pattern for Plasmodium and Haemoproteus, however low prevalence and high diversity were recorded in areas considered as a hotspot of biodiversity in Central Chile. Our findings confirmed the importance of habitat and climatic variables explaining prevalence, diversity and distribution of haemosporidian parasites in a huge latitudinal gradient, belonging the distribution of the Thorn-tailed Rayadito in the world's southernmost forests ecosystems.
Keywords: latitudinal gradient; haemosporidian parasites; leucocytozoon; plasmodium; haemoproteus; south american temperate forests